2009
DOI: 10.2174/138161209789909719
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 and Renal Function in Older Adults

Abstract: Chronic kidney disease (CKD) is a major public health problem and can result in end-stage renal disease with need for dialysis or transplantation. In Europe up to 12% of the adult population had some renal impairment, while in the United States the end stage of CKD has increased dramatically from 209.000 in 1991 to 472.000 in 2004. Diabetes and hypertension are major causes of kidney pathology. Infection, particularly ascending infection, is more common with increasing age, as both immune function declines and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 77 publications
2
9
0
Order By: Relevance
“…Chronic kidney disease (CKD) commonly requires dialysis or transplantation for patients' survival and can eventually lead to dead [185,186]. It has been reported that, because of their anti-inflammatory properties, omega-3 fatty acids can also preserve kidneys.…”
Section: Prevention Of Kidney Diseasesmentioning
confidence: 99%
“…Chronic kidney disease (CKD) commonly requires dialysis or transplantation for patients' survival and can eventually lead to dead [185,186]. It has been reported that, because of their anti-inflammatory properties, omega-3 fatty acids can also preserve kidneys.…”
Section: Prevention Of Kidney Diseasesmentioning
confidence: 99%
“…Studies in animals have shown that omega-3 FA can be beneficial in retarding the progression of renal failure [ 34 , 35 ]. Epidemiological studies suggest that omega-3 FA can slow the progression of renal dysfunction [ 36 , 37 ] and prevent the decline in creatinine clearance in healthy elderly people [ 38 ]. In addition, omega-3 FA could slow the progression of proteinuria in patients with type 2 diabetes, but the study in question included patients who were not controlling their BP [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic kidney disease (CKD) is one of the most important public health problems which leads to dialysis and transplantation ( 12 ). The incidence of cardiac death in dialysis and transplant patients is higher than the general population which can be attributed to hyperlipidemia, hypertension, diabetes mellitus, smoking and other reasons ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the common problems in patients before and after kidney transplantation are lipid abnormalities which can lead to development and progression of CVR and chronic graft dysfunction ( 14 ). Oxidative stress causes the most pathological changes in the kidney, initially followed by an inflammatory reaction ( 12 ). Some studies demonstrated the effect of omega-3 on dyslipidemia, lipid and protein peroxidation, and antioxidant and anti-inflammatory defense in patients with chronic renal failure (CRF) ( 15 - 18 ).…”
Section: Discussionmentioning
confidence: 99%